Simultaneous Saccharification and Fermentation for Ethanol Production from Rice Straw by Candida shehatae and Saccharomyces cerevisiae - Marika Ngamsirisomsakul (Science Faculty of Chiang Mai University, 2019)
Ethanol production from rice straw using simultaneous saccharification and fermentation (SSF) was presented in comparison with its variation, semi-SSF (sSSF) in order to explore any potential improvement in ethanol production and conversion of cellulosic sugars. Neither significant differences in term of ethanol concentration nor improvement in overall productivity when using sSSF and SSF were observed in this study. Similar ethanol concentration of approximately 12 g/L was obtained in all cases using Candida shehatae ATCC 22984, Saccharomyces cerevisiae TISTR 5339 and co-cultivation of both strains, although lower productivity was evident when using C. shehatae. Furthermore, sequential fermentation of C. shehatae followed by S. cerevisiae with added cellulase had demonstrated its potential application in fermentation that fully converted xylose and glucose into ethanol.